2013
DOI: 10.1002/dvdy.24007
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Hox gene expression and activity to build the vertebrate axial skeleton

Abstract: It has long been known that Hox genes are central players in patterning the vertebrate axial skeleton. Extensive genetic studies in the mouse have revealed that the combinatorial activity of Hox genes along the anterior-posterior body axis specifies different vertebral identities. In addition, Hox genes were instrumental for the evolutionary diversification of the vertebrate body plan. In this review, we focus on fundamental questions regarding the intricate mechanisms controlling Hox gene activity. In particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 127 publications
0
43
0
6
Order By: Relevance
“…In agreement with this interpretation of our data, there is increasing evidence that the timely activation of Hox genes is critical for proper anterior-posterior patterning (see review by ref. 40). For instance, deletion of the Hoxc8 enhancer (41), or deletion of the Hoxd10 enhancer (42), leads to a temporal delay in activation of the respective Hox gene and anterior shifts in body segment identity.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this interpretation of our data, there is increasing evidence that the timely activation of Hox genes is critical for proper anterior-posterior patterning (see review by ref. 40). For instance, deletion of the Hoxc8 enhancer (41), or deletion of the Hoxd10 enhancer (42), leads to a temporal delay in activation of the respective Hox gene and anterior shifts in body segment identity.…”
Section: Discussionmentioning
confidence: 99%
“…However, they produce skeletal elements with unique anatomical features characteristic of their position along the anteriorposterior body axis. This regional differentiation of somites is to a large extent under the control of Hox genes (Pearson et al, 2005;Mallo et al, 2010;Casaca et al, 2014). In mammals, the Hox gene family is composed of 39 members distributed in four gene clusters resulting from two consecutive duplications of an ancestral cluster.…”
Section: Introductionmentioning
confidence: 99%
“…This led to the classification of Hox genes into 13 groups, normally known as paralog groups (PGs) (Prince, 2002;Duboule, 2007). A variety of genetic studies revealed that Hox proteins have a high degree of functional specificity, often shared by the different members of the same PG (Casaca et al, 2014). It is thought that morphological diversity in the axial skeleton results from the combined activities provided by the different Hox PGs (Mallo et al, 2009;Wellik, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the genetic causes of intraspecific tail length polymorphism would be one essential step toward elucidating the mechanisms underlying the development and evolution of tails. In laboratory mice, genetic studies of axial skeleton development have identified multiple genes and mutations involved in caudal vertebra development that have pleiotropic effects on fertility, somitogenesis, and meiotic recombination, thus shedding light on vertebrate evolution2345. However, given the tremendous variety of tail morphology found in animals, mice alone may not be able to capture the full spectrum of the evolutionary diversity of mammalian tails.…”
mentioning
confidence: 99%